2010
DOI: 10.1182/blood-2009-07-235531
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell transplantation in multiple myeloma: impact of response failure with thalidomide or lenalidomide induction

Abstract: Autologous stem cell transplantation as a platform for multiple myeloma treatment is the standard of care for patients who can safely withstand the procedure. Before novel agents were introduced, onethird to one-half of patients did not achieve partial response at transplantation. Previous medical literature has shown that in this past era, absence of initial response to induction therapy had no impact on progression-free survival and overall survival after highdose therapy. Lack of response to initial inducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 30 publications
5
27
1
Order By: Relevance
“…In comparison with our previous study, we observed higher frequencies of remission with both novel therapies and HDT. Calculations of survival after a landmark of 1 year, and the infrequency of censored data, contributed to the more marked differences in survival now observed for patients with NR, PR and CR in comparison with our previous report; 9 these results supported further the conclusion of Lahuerta et al 19 and of Gertz et al 20 on the importance of CR and PR on survival. Persistent NR was the most immediate and ominous problem that prevailed in only 10% of patients treated with recent programs, whose survival remained short and similar to that described by Snapper 50 years ago for patients unable to receive effective therapy.…”
Section: Discussionsupporting
confidence: 81%
“…In comparison with our previous study, we observed higher frequencies of remission with both novel therapies and HDT. Calculations of survival after a landmark of 1 year, and the infrequency of censored data, contributed to the more marked differences in survival now observed for patients with NR, PR and CR in comparison with our previous report; 9 these results supported further the conclusion of Lahuerta et al 19 and of Gertz et al 20 on the importance of CR and PR on survival. Persistent NR was the most immediate and ominous problem that prevailed in only 10% of patients treated with recent programs, whose survival remained short and similar to that described by Snapper 50 years ago for patients unable to receive effective therapy.…”
Section: Discussionsupporting
confidence: 81%
“…14 A number of studies since have further reported that achievement of CR or stringent CR was associated with improved long-term outcomes when compared with lesser degrees of response with NA induction. 4,7 Despite these reported associations, additional pretransplant salvage chemotherapy in patients who did not achieve PR post-induction did not improve OS or PFS, even when deeper pretransplant responses were achieved. 15 The different implications of post-induction response reported across studies may reflect differences in study population, underlying disease heterogeneity in myeloma or the weaker predictive value of post-induction response.…”
Section: Discussionmentioning
confidence: 86%
“…[4][5][6][7] However, the outcomes of the group of patients who respond are heterogeneous; some patients relapse within a year and have very poor survival despite achieving deep responses. [8][9][10] It is unknown whether depth of response or early loss of response is a more important predictor of survival as both factors have not been compared directly in studies.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] Nevertheless, the type of response achieved with novel agents as induction before ASCT might have an important prognostic impact. 15 Combinations that use novel agents, including bortezomibbased therapy, are currently evaluated as induction treatment before ASCT, with the objective of increasing the CR or CR plus VGPR rate both before and after ASCT. [16][17][18] In this setting, the recent phase 3 study by the Intergroupe Francophone du Myélome (IFM2005-01; NCT00200681) demonstrated the superiority of bortezomibdexamethasone induction before HDT-ASCT compared with vincristine-adriamycin-dexamethasone (VAD), the previous standard of care.…”
Section: Introductionmentioning
confidence: 99%